Pemanfaatan Konten Video dalam Program MBKM di Humas Bawaslu sebagai Bentuk Sosialisasi Politik Digital bagi Generasi Z - Elsa Meyla Audina (CV. Kurnia Grup, 2026)
The utilization of video content among Gen Z as a form of learning about the electoral process on social media can be strategically employed for civic education, provided it is supported by high quality educational content, digital literacy, and collaboration between the KPU, Bawaslu, educational institutions, influencers, and social media platforms. Thus, Gen Z can learn more about elections through social media, not only as a space for political campaigning but also as a digital space for political education. Research indicates that Gen Z tends to access political information through visual, interactive, and fast paced content, with primary platforms such as TikTok, Instagram, and X. Gen Z is more interested in short videos, reviews, light hearted content, and creative material produced by political influencers or election related institutions; therefore, electoral content presented in similar formats holds great potential to capture attention and broaden the scope of political learning. However, without proper digital literacy guidance, Gen Z often reads only the appealing text or watches entertaining clips without verifying the information, making them vulnerable to propaganda and disinformation.